Low-dose vs. standard-dose intravenous alteplase for acute ischemic stroke with unknown time of onset - Wang, Zekun; Ji, Kangxiang; Fang, Qi (Frontiers in Neurology, 2023)
Background Standard-dose intravenous alteplase for acute ischemic stroke (AIS) in the unknown or extended time window beyond 4.5 h after symptom onset is both effective and safe for certain patients who were selected based on multimodal neuroimaging. However, uncertainty exists regarding the potential benefit of using low-dose alteplase among the Asian population outside the 4.5-h time window. Methods Consecutive AIS patients who received intravenous alteplase between 4.5 and 9 h after symptom onset or with an unknown time of onset guided by multimodal computed tomography (CT) imaging were identified from our prospectively maintained database. The primary outcome was excellent functional recovery, defined as having a modified Rankin scale (mRS) score of 0–1 at 90 days. Secondary outcomes included functional independence (an mRS score of 0–2 at 90 days), early major neurologic improvement (ENI), early neurologic deterioration (END), any intracranial hemorrhage (ICH), symptomatic ICH (sICH), and 90-day mortality. Propensity score matching (PSM) and multivariable logistic regression models were used to adjust for confounding factors and compare the clinical outcomes between the low- and standard-dose groups. Results From June 2019 to June 2022, a total of 206 patients were included in the final analysis, of which 143 were treated with low-dose alteplase and 63 were treated with standard-dose alteplase. After accounting for confounding factors, we observed that there were no statistically significant differences between the standard- and low-dose groups with respect to excellent functional recovery [adjusted odds ratio = 1.22 (aOR), 95% confidence interval (CI): 0.62–2.39; adjusted rate difference (aRD) = 4.6%, and 95% CI: −11.2 to 20.3%]. Patients of both groups had similar rates of functional independence, ENI, END, any ICH, sICH, and 90-day mortality. In the subgroup analysis, patients aged ≥70 years were more likely to achieve excellent functional recovery when receiving standard-dose rather than low-dose alteplase. Conclusion The effectiveness of low-dose alteplase might be comparable to that of standard-dose alteplase in AIS patients aged <70 years with favorable perfusion-imaging profiles in the unknown or extended time window but not in those aged ≥70 years. Furthermore, low-dose alteplase did not significantly reduce the risk of sICH compared to standard-dose alteplase.